Self-assembly with degenerate prototropy - Baruah, Pranjal K.; Gonnade, Rajesh G.; Phalgune, U. D.; Sanjayan, G. J. (Journal of Organic Chemistry, 2005)
This work describes a rational approach for addressing the prototropy-related problems in heterocycle-based self-assembling systems by the use of degenerate prototropy. As a proof of principle, the utility of degenerate prototropy is demonstrated herein by developing heterocycle-based AADD-type self-assembling modules that exist as ``single set of protameric pair (duplex)'' in both solution and solid states. These self-assembling modules are quickly accessible in good yield by reacting 2-amino-5,5-disubstituted-1H-pyrimidine-4,6-diones, available in one step by the condensation of (x,a-dialkyl malonates and free guanidine, with isocyanates. Evidence from NMR spectroscopy, ESI mass spectrometry, and single-crystal X-ray diffraction studies confirmed the formation of molecular duplexes. The effect of electronic repulsion in duplex formation is also investigated. Their ready synthetic accessibility, remarkably high propensity to crystal formation, and the novel property of degenerate prototropy would make these novel self-assembling molecules promising candidates for many proposed applications.

Short S=O center dot center dot center dot C=O contacts associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate in their inclusion complexes - Manoj, Kochunnoonny; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Crystal Growth & Design, 2005)
Diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate are linked via short S=O&BULL;&BULL;&BULL; C=O contacts ranging from 2.890 to 3.140 &ANGS; (sum of the van der Waals radii of O and C atoms 3.22 &ANGS;) in all the inclusion complexes formed with organic guest solvents having a C2 symmetry. Although a search for S= O&BULL;&BULL;&BULL; C=O interactions in the CSD showed a sizable number of structures, this communication recognizes its significance for the first time in the formation of molecular assemblies. In all the crystals in the present study except the solvent-free form, the S=O bond points almost perpendicularly to the Csp2 atom of the C=O group. This was also the most frequently observed geometrical approach in CSD analysis. The solvent-free form shows dimer formation via C-H&BULL;&BULL;&BULL; O interaction, which has longer S=O&BULL;&BULL;&BULL; C=O contacts.

Sulfonate protecting groups. synthesis of O- and C-methylated inositols: D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether - Sarmah, M. P.; Shashidhar, M. S.; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
Syntheses of D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether starting from myo-imositol are described. One or two of the inyo-inositol 1,3,5-orthoformate hydroxyl groups were protected as tosylates. These mono or ditosylates served as key intermediates for the preparation of O- and C-methyl inositols. Racemic 2,4-di-O-tosyl-myo-inositol 1,3,5-orthoformate was resolved as its diastereomeric camphanates. Use of sulfonate groups for the protection of inositol hydroxyl groups resulted in substantial improvement in the overall yield of O- and C-methyl inositols. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Orthoester; Protecting group; sulfonate

Stereoselective syntheses of unnatural steroidal C(20R) aldehydes by ionic hydrogenation of C-20 tertiary alcohols - Shingate, Bapurao B.; Hazra, Braja G.; Pore, Vandana S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron Letters, 2006)
Syntheses of three unnatural steroidal C(20R) aldehydes have been realised from 16-dehydropregnenol one acetate. The salient feature of the synthesis is the ionic hydrogenation of C-20 tertiary alcohols leading to the formation of the C(20R) unnatural isomer with complete stereoselectivity. Oxidative hydrolysis of the dithiane moiety furnished the C(20R) aldehydes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-dithiane; ionic hydrogenation; oxidative hydrolysis; stereoselective synthesis; unnatural C-20 aldehydes

Subtle crossover from C-H center dot center dot center dot O to S=O center dot center dot center dot C=O short contacts in the association of diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate upon format - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystal Growth & Design, 2006)
Diastereomers of 2,4(6)- di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate associate via weak interactions to form ``head-to-head'' dimers in their crystals. Molecular association through C-H center dot center dot center dot O short contacts do not leave any void for the guest inclusion, while association through S=O center dot center dot center dot C=O bridging produces pseudopolymorphs. Three crystalline modifications are observed for the title compound: form I, monoclinic P2(1), without any guest solvent, and solvated forms II and III, that belong to monoclinic space groups P2(1) and C2, respectively. A majority of solvates, which include pyridine, dichloromethane, benzene, tetrahydrofuran, and cyclohexanone as guests, belong to form III. All these guests have 2-fold symmetry axes ( C2) with their electron count within 40-62 electrons; guest selectivity experiments indicate that planar aromatic guests ( pyridine, benzene) bind better to the host molecules as compared to nonplanar guests ( dioxane, cyclohexanone). The molecular packing that is created thorough channels in the crystal ( avoiding interpenetration of the layers) are of interest because of their potential application in molecular separation by forming selective inclusions. The diastereomeric association via S=O center dot center dot center dot C=O dipolar short contacts, a consistent feature observed in all the solvates, is thought to have relevance in the binding of sulfonyl drugs to the C=O moieties of the receptor proteins.

Synthesis of the spiro fused beta-lactone-gamma-lactam segment of oxazolomycin - Mohapatra, Debendra K.; Mondal, Dhananjoy; Gonnade, Rajesh G.; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
An effective synthetic strategy for construction of the novel spiro-bicyclic beta-lactone-gamma-lactam system present in oxazolomycin has been demonstrated. The 3,4-disubstituted pyrrolidine ring system was constructed via an Evans aldol reaction. The spiro-beta-lactone ring was elaborated from a gem-hydroxymethyl moiety that was successfully installed by an aldol followed by a crossed Cannizzaro reaction. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: crossed Cannizzaro reaction; Evans' aldol reaction; Garner's aldehyde; intramolecular Mitsunobu reaction; ruthenium tetroxide oxidation

Steric control in pd-mediated cycloisomerization of sugar alkynols: documentation of a rare allylic epimerization - Ramana, Chepuri V.; Patel, Pitarnbar; Gonnade, Rajesh G. (Tetrahedron Letters, 2007)
Pd-mediated cycloisomerization of C3-alkynylated glucofuranosyl derivatives revealed a dominance of steric factors over electronic factors. However, the intermediate glycals were epimerized prior to the ketalization and afforded the more stable cis-fused bicyclic ketals. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bis-Homopropargylic Alcohols; Oriented Organic-Synthesis; Nucleophilic-Attack; Room-Temperature; Palladium; Chemistry; Heterocycles; Complexes; Transformations; Sonogashira

Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Stereoselective synthesis of beta-C-Allyl- and beta-C-propargyl-D-arabinofuranosides - Ramana, C. V.; Narute, Sachin B.; Gonnade, Rajesh G.; Patil, Rahul S. (Synthesis-Stuttgart, 2008)
The stereoselective synthesis of beta-configured C-allyl- and C-propargyl-D-arabinofuranosides (4,7-anhydro-1,2,3-deoxy-D-gluco-oct-1-enitols and -oct-1-ynitols) was addressed by employing allylation/propargylation of a dialdofuranose under aqueous Barbier reaction conditions and acid-catalyzed furan ring transposition of 5-O-mesyl-manno-oct-7-eno- or 5-O-mesyl-manno-oct-7-ynofuranoside derivatives.
Keywords: Allylation; Barbier reaction; C-glycoside; D-mannose; propargylation; Ring transposition

Synthesis and biological evaluation of bile acid dimers linked with 1,2,3-triazole and bis-beta-lactam - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit; Gonnade, Rajesh G. (Organic & Biomolecular Chemistry, 2008)
We report herein the synthesis and biological evaluation of bile acid dimers 11-18 linked through 1,2,3-triazole and bis-beta-lactam. The dimers 11-18 were synthesized using 1,3-dipolar cycloaddition reaction of diazido bis-beta-lactams 3, 4 and terminal alkynes 7-10 derived from cholic acid/deoxycholic acid in the presence of Cu(I) catalyst (click chemistry). These novel molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal as well as antibacterial activity against all the tested fungal and bacterial strains. Moreover, their in vitro cytotoxicities towards HEK-293 and MCF-7 cells were also established.

Stereoselective construction of steroidal side chain from 16-dehydropregnenolone acetate - Aher, Nilkanth G.; Gonnade, Rajesh G.; Pore, Vandana S. (Synlett, 2009)
Stereoselective construction of steroidal side chain at C-20 having `natural' configuration using 16-dehydropregnalone acetate (16-6PA) as a starting material has been carried out. Palladium-catalyzed carbon-carbon bond-forming Heck reaction between C-20 vinyl iodide with methyl acrylate and transfer hydrogenation with triethylsilane and Pd/C are the key steps for stereoselective side-chain synthesis.
Keywords: 16-dehydropregnenolone acetate; Heck coupling; stereoselectivity; steroidal side chain; transfer hydrogenation

Synthesis, resolution, and applications of 3-amino-2,2-dimethy1-1,3-diphenylpropan-1-ol, a conformationally restricted 1,3-aminoalcohol - Patil, M. N.; Gonnade, Rajesh G.; Joshi, Navalkishore N. (Tetrahedron, 2010)
Efficient synthetic routes to both syn and anti diastereomers of a conformationally restricted 1,3-aminoalcohol were devised. Resolution of the aminoalcohols was accomplished through diastereomeric salt with R-(-)-O-acetyl mandelic acid. These aminoalcohols were examined as ligands for two standard reactions, namely, enantioselective addition of Et(2)Zn to aldehydes and reduction of prochiral ketones with BH(3). (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-Aminoalcohol; Aldol-Tishchenko reaction; Diethylzinc; Oxazaborinane; Resolution

Solvent induced crystallization of 1,2,3,4(6),5-penta-O-acetyl-6(4)-O-[(1S)-10-camphor sulfonyl]-myo-inositol diastereomers associated via weak trifurcated C-H center dot center dot center dot O interactions - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (CrystEngComm, 2012)
The title compound produced three different types of solvent inclusion crystals having a conserved dimeric association via trifurcated C-H center dot center dot center dot O interactions between the diastereomers. These `dimeric' units are organized differently to produce three crystal types containing guest molecules. In type I and II, unit translated dimers created voids for guest inclusion, whereas in type III the guest sites were produced by helical association of dimers. Inclusion of dichloromethane gave two different types of crystals; however, we were unable to obtain unsolvated crystals of the title compound.

Strength from weakness: the role of CH center dot center dot center dot N hydrogen bond in the formation of wave-like topology in crystals of aza-heterocycles - Shivakumar, Kota; Vidyasagar, Adiyala; Naidu, Andra; Gonnade, Rajesh G.; Sureshan, Kana M. (Crystengcomm, 2012)
Crystal engineering has succeeded in the design and construction of various architectures such as tapes, ribbons, rosettes, layers etc. Though wavy layer packing is known to occur in crystals, no crystal engineering attempts have been ventured to create wavy layer topology in crystals. Aromatic nitrogen heterocyclics (ANHs) are known to preferentially self assemble in lateral fashion through edge-to-edge CH center dot center dot center dot N hydrogen bonds. Exploiting this preferential lateral assembly of ANHs, we have engineered wavy layer architectures in the crystals of various substituted quinolines.

Synthesis of the aminocyclitol units of (-)-hygromycin a and methoxyhygromycin from myo-inositol - Gurale, Bharat P.; Shashidhar, Mysore S.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2012)
Concise and efficient syntheses of the aminocyclitol cores of hygromycin A (HMA) and methoxyhygromycin (MHM) have been achieved starting from readily available myo-inositol. Reductive cleavage of myo-inositol orthoformate to the corresponding 1,3-acetal, stereospecific introduction of the amino group via the azide, and resolution of a racemic cyclitol derivative as its diastereomeric mandelate esters are the key steps in the synthesis. Synthesis of the aminocyclitol core of hygromycin A involved chromatography in half of the total number of steps, and the aminocyclitol core of methoxyhygromycin involved only one chromatography.

Switching the H-bonding network of a foldamer by modulating the backbone chirality and constitutional ratio of amino acids - Ramesh, Veera V. E.; Vijayadas, Kuruppanthara N.; Dhokale, Snehal A.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
This communication describes the folding propensity of a hetero-foldamer motif featuring proline (Pro) and anthranilic acid (Ant) residues in a 1:2:1 (alpha: beta: alpha) constitutional ratio. Structural investigations unequivocally suggest that the hydrogen-bonding network of this foldamer motif can be switched between 9-membered and 6-membered by modulating the backbone chirality and constitutional ratio of the amino acid residues.

Syntheses and determination of absolute configurations and biological activities of the enantiomers of the longtailed mealybug pheromone - Ramesh, Remya; Swaroop, Pandrangi Siva; Gonnade, Rajesh G.; Thirupath, Choppari; Waterworth, Rebeccah A.; Millar, Jocelyn G.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2013)
Preparation and assignment of absolute configurations to both enantiomers of the sex pheromone of the longtailed mealybug, an irregular monoterpenoid with extraordinary biological activity, has been completed. Comparison of the biological activities of both enantiomers and the racemate in field trials showed that the (S)-(+)-enantiomer was highly attractive to male mealybugs, strongly suggesting that female longtailed mealybugs produce this enantiomer. The (R)-(-)-enantiomer was benign, being neither attractive nor inhibitory.

Synthesis and antitubercular activity of amino alcohol fused spirochromone conjugates - Mujahid, Mohammad; Gonnade, Rajesh G.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, Murugan (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 21 new amino alcohol fused spirochromone conjugates have been synthesized, characterized with analytical data and evaluated their antimycobacterial activity against Mycobacterium tuberculosis (virulent strain H37Rv) in vitro. Some of the compounds exerted significant inhibition, in particular, compound 4f found to be the most potent derivative exhibiting MIC = 3.13 mu g/mL. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amino alcohol; Antitubercular activity; Mycobacterium tuberculosis; Spirochromones

Synthesis and structural studies of S-type/N-type-locked/frozen nucleoside analogues and their incorporation in RNA-selective, nuclease resistant 2 `-5 ` linked oligonucleotides - Erande, Namrata D.; Gunjal, Anita D.; Fernandes, Moneesha; Gonnade, Rajesh G.; Kumar, Vaijayanti A. (Organic & Biomolecular Chemistry, 2013)
2'-endo locked or frozen (S-type)/3'-endo locked or frozen (N-type) nucleoside analogues were synthesized. Conformational analysis based on (3)J(HH) and NOE measurements is presented which is further confirmed by X-ray crystal structural studies. 2'-5' isoDNA oligonucleotides (ON) were synthesized using these modified nucleoside analogues and UV-T-m studies of the resultant 2'-5' isoDNA : RNA duplexes reflect the site-and sequence-dependent effects and confirm that the S-type sugar conformations were preferred over the N-type sugar geometry in such duplexes.

Synthesis of 3,5-Bis(acrylaldehyde) boron-dipyrromethene and application in detection of cysteine and homocysteine in living cells - Madhu, Sheri; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Journal Of Organic Chemistry, 2013)
Synthesis, characterization, and spectral and electrochemical properties of 3,5-bis(acrylaldehyde) BODIPY are described. The compound exhibited higher selectivity toward cysteine/homocysteine than toward other amino acids and thiol-containing compounds as shown by absorption and emission titration experiments and by experiments in living cells.

Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Stereospecific synthetic approach towards tamiflu using the ramberg-backlund reaction from cysteine hydrochloride - Chavan, Subhash P.; Chavan, Prakash N.; Gonnade, Rajesh G. (RSC Advances, 2014)
The stereospecific formal synthesis of Tamiflu from L-cysteine hydrochloride as the chiral source is described. The notable feature of the present strategy is the Ramberg-Backlund reaction and Sharpless-Reich protocol as the key chemical transformations to access the cyclohexene skeleton of Tamiflu.

Synthesis, structure, spectral, electrochemical and sensing properties of 3-amino boron-dipyrromethene and its derivatives - Ganapathi, Emandi; Madhu, Sheri; Chatterjee, Tamal; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Dyes and Pigments, 2014)
We report the synthesis of 3-amino boron-dipyrromethene (3-amino BODIPY) by treating 3-bromo boron-dipyrromethene (3-bromo BODIPY) initially with sodium azide in acetonitrile followed by tri-phenylphosphine(PPh3)/H2O in tetrahydrofuran in three steps under mild reaction conditions. In this reaction, 3-azido BODIPY which formed in the first step was not isolated but the 3-iminophosphorane BODIPY which formed in the second step was isolated and characterized crystallographically. The 3-amino BODIPY was characterized by various spectroscopic and X-ray analytical techniques. To test the reactivity of amine functionality on BODIPY core, we prepared 1-(meso-anisyl BODIPY)-3-phenyl urea/thiourea derivatives under simple reaction conditions. Our studies indicated that 1-(meso-anisyl BODIPY)-3-pheny thiourea can act as specific chemodosimetric sensor for Hg2+ ion and 1-(meso-anisyl BODIPY)-3-phenyl urea as colorimetric and ratiometric sensor for F- ion. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: 3-Amino boron dipyrromethene; Chemodosimeter; F sensor; Fluorescent probes; Iminophosphorane BODIPY; Mercury(II) sensor

Synthesis, DNA interaction and anticancer activity of 2-anthryl substituted benzimidazole derivatives - Sontakke, Vyankat A.; Kate, Anup N.; Ghosh, Sougata; More, Piyush; Gonnade, Rajesh G.; Kumbhar, Navanath M.; Kumbhar, Anupa A.; Chopade, Balu Ananda; Shinde, Vaishali S. (New Journal of Chemistry, 2015)
2-Anthryl benzimidazole derivatives (5-7) with hydrogen, carboxyl and benzoyl substituents at the 5th position have been synthesized using a silica supported periodic acid catalyst. The DNA cleavage activity of 5-7 was studied in the presence of light using pBR322 plasmid DNA and was shown to vary with substitution at the 5th position of benzimidazole derivatives. DNA binding studies using ethidium bromide displacement assay demonstrated the non-intercalative binding mode of 5-7. The anticancer activity of these target molecules was tested against MCF-7 and HL-60 cell lines, and they exhibited remarkable activity in the micromolar range. Cellular uptake and morphological changes were confirmed by fluorescence and confocal microscopy. A molecular docking study was carried out to explore the DNA binding mechanism of 5-7.

Synthesis of naturally occurring (+)-osmundalactone and 4-epi-(+)-osmundalactone from triacetyl-O-D-glucal - Kotammagari, Tharun K.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Tetrahedron Letters, 2015)
An efficient total synthesis of (+)-osmundalactone 1 has been achieved starting from readily available triacetyl-O-D-glucal 6 employing Ferrier rearrangement and Jones oxidation as key steps. Also, synthesis of 4-epi-(+)-osmundalactone 2 was accomplished from the common key intermediate 9. The absolute stereochemistry of (+)-osmundalactone 1 and a precursor of 4-epi-(+)-osmundalactone 2 have been established by single crystal X-ray analysis. The overall yield of compound 1 and 2 from triacetyl-O-D-glucal 6 is 13% and 8%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bioactive molecules; carbohydrates; D-glucal; Ferrier rearrangement; Pyrones

Synthesis of novel N-cyclopentenyl-lactams using the aube reaction - Shinde, Madhuri V.; Ople, Rohini S.; Sangtani, Ekta; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Beilstein Journal of Organic Chemistry, 2015)
A novel and convenient method utilizing the Aube reaction to access a new class of compounds that are similar to carbocyclic nucleosides is reported. The azido alcohol derived from Vince lactam undergoes the Aube reaction with various cyclic ketones to give cyclopentenyl-substituted lactams. Upon dihydroxylation, this affords the N-cyclopentenyl-lactam compounds in racemic form. Given the numerous uses of nucleosides and related compounds, we were interested in the synthesis of carbocylic nucleoside mimics. The attempts and results are described herein.
Keywords: Aube reaction; Biological activity; carbocyclic nucleosides; cyclopentenylated lactams; cyclopentylated lactams

Selective synthesis of N-unsubstituted and N-arylindoles by the reaction of arynes with azirines - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; "Jain, Shailja"; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2016)
The transition-metal-free and temperature-dependent highly selective reaction of arynes with 2H-azirines allowing the synthesis of either N-unsubstituted or N-arylindoles has been developed. At 60 degrees C, arynes generated from 2-(trimethylsilyl)aryl triflates smoothly insert into 2H-azirines to form 2,3-diarylindoles with high selectivity. Interestingly, when the reaction was performed at -10 degrees C, the selectivity was switched to the formation of 1,2,3-triarylindoles in good yields.

Substrate-controlled selectivity switch in the three-component coupling involving arynes, aromatic tertiary amines, and CO2 - Bhojgude, Sachin Suresh; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
The transition-metal-free multicomponent coupling involving arynes, aromatic tertiary amines, and CO2 is reported. The reaction exhibits switchable selectivity depending on the electronic nature of the aromatic amines used. With amines bearing electron-releasing/neutral groups as the nucleophilic trigger, the reaction afforded 2-arylamino benzoates via a nitrogen to oxygen alkyl group migration. Employing electron-deficient amines in the reaction furnished 2-aminoaryl benzoates proceeding via the aryl to aryl amino group migration resembling a Smiles rearrangement.

Synthesis of 4H-chromenes by an unexpected, K3PO4-mediated intramolecular rauhut–currier type reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2016)
In an attempt to develop the umpolung of Michael acceptors using chalcones having an enoate moiety under N-heterocyclic carbene (NHC) catalysis, a K3PO4-mediated intramolecular Rauhut–Currier type reaction was observed. This C(sp2)–C(sp2) coupling reaction afforded the biologically important 4H-chromenes in moderate to good yields. It is likely that the enol ether functionality acts as the nucleophilic trigger in this reaction.

Synthesis of functionalized amino epoxides by a three-component coupling involving aziridines, arynes and aldehydes - Roy, Tony; Thangaraj, Manikandan; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2016)
A transition-metal-free three-component coupling involving N-substituted aziridines, arynes and aldehydes resulting in the formation of trisubstituted N-aryl alpha-amino epoxides has been demonstrated. The reaction likely proceeds via the highly strained cyclic nitrogen ylide intermediates generated from aziridines and arynes.

Synthesis of quinoline-based NNN-pincer nickel(II) complexes: a robust and improved catalyst system for C–H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Pandey, Dilip K.; Gonnade, Rajesh G.; Punji, Benudhar (Organometallics, 2016)
The quinoline-based pincer nickel(II) complexes κN,κN,κN-{R2N-C6H4-(μ-N)-C9H6N}NiX ((R2NNNQ)NiCl: R = Me, 2a; R = Et, 2b) were synthesized by the reaction of the ligand precursors (R2NNNQ)H (R = Me, 1a; R = Et, 1b) with (DME)NiCl2 in the presence of Et3N. Similarly, the pincer nickel(II) derivatives (R2NNNQ)NiX (R = Me, X = Br, 3a; R = Et, X = Br, 3b; R = Me, X = OAc, 4a) were obtained by treatment of the ligands (R2NNNQ)H with the nickel precursor (THF)2NiBr2 or Ni(OAc)2. All of these complexes were characterized by 1H and 13C NMR spectroscopy as well as by elemental analysis. Further, the molecular structures of 2a and 3a,b were elucidated by X-ray crystallography. Complex 2a is found to be an efficient catalyst for the direct C–H bond alkylation of substituted benzothiazoles and oxazoles with various unactivated alkyl halides containing β-hydrogens under mild reaction conditions. The catalyst 2a is very robust and was recycled and reused five times for the alkylation reaction without a decrease in its catalytic activity. Preliminary studies reveal that the catalyst 2a acts as an active catalyst and the alkylation reaction appears to operate via a radical pathway.

Salts and cocrystals of furosemide with pyridines: differences in π-Stacking and color polymorphism - Sangtani, Ekta; Mandal, Suman Kumar; Sreelakshmi, A. S.; Munshi, Parthapratim; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Furosemide (FS), a loop diuretic drug that has a potential to exhibit polymorphism, produced color polymorphs of orange (form 1I) and yellow (form 1II) concomitantly with coformer 1, 2-bis(4-pyridyl)ethylene. However, cocrystallization of FS with other pyridines yielded colorless salts (2 and 4) and cocrystals (3 and 5). The significant color difference between the two polymorphs (forms 1I and 1II) could be attributed to the dissimilar π-stacking patterns between the two components and differences in their highest occupied molecular orbital−lowest unoccupied molecular orbital gap. The molecular packing of form 1I and 2 is very similar, but 2 is colorless due to lack of extended π-conjugation.

Self-assembly of fluorinated sugar amino acid derived alpha,gamma-cyclic peptides into transmembrane anion transport - Burade, Sachin S.; Saha, Tanmoy; Bhuma, Naresh; Kumbhar, Navanath; Kotmale, Amol; Rajamohanan, Pattuparambil R.; Gonnade, Rajesh G.; Talukdar, Pinaki; Dhavale, Dilip D. (Organic Letters, 2017)
Syntheses of fluorinated sugar amino acid derived alpha,gamma-cyclic tetra- and hexapeptides are reported. The IR, NMR, ESI-MS, CD, and molecular modeling studies of cyclic tetra- and hexapeptides showed C-2 and C-3 symmetric flat oval- and triangular-ring shaped, beta-strand conformations, respectively, which appear to self assemble into nanotubes. The alpha,gamma-cyclic hexapeptide (EC50 = 2.14 mu M) is found to be a more efficient ion transporter than alpha,gamma-cyclic tetrapeptide (EC50 = 14.75 mu M). The anion selectivity and recognition of alpha,gamma-cyclic hexapeptide with NO3- ion is investigated.

Specific stereoisomeric conformations determine the drug potency of cladosporin scaffold against malarial parasite - Das, Pronay; Babbar, Palak; Malhotra, Nipun; Sharma, Manmohan; Jachak, Goraknath R.; Gonnade, Rajesh G.; Shanmugam, Dhanasekaran; Harlos, Karl; Yogavel, Manickam; Sharma, Amit; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2018)
The dependence of drug potency on diastereomeric configurations is a key facet. Using a novel general divergent synthetic route for a three-chiral center antimalarial natural product cladosporin, we built its complete library of stereoisomers (cladologs) and assessed their inhibitory potential using parasite-, enzyme-, and structure-based assays. We show that potency is manifest via tetrahyropyran ring conformations that are housed in the ribose binding pocket of parasite lysyl tRNA synthetase (KRS). Strikingly, drug potency between top and worst enantiomers varied 500-fold, and structures of KRS-cladolog complexes reveal that alterations at C3 and C10 are detrimental to drug potency whereas changes at C3 are sensed by rotameric flipping of glutamate 332. Given that scores of antimalarial and anti-infective drugs contain chiral centers, this work provides a new foundation for focusing on inhibitor stereochemistry as a facet of antimicrobial drug development.

Studies on CL-20/HMX (2:1) cocrystal: a new preparation method and structural and thermokinetic analysis - Ghosh, Mrinal; Sikder, Arun K.; Banerjee, Shaibal; Gonnade, Rajesh G. (Crystal Growth & Design, 2018)
A new preparation method for CL-20/HMX (2:1) cocrystal has been established at the laboratory level that is amenable for scale up. Solvent evaporation from a saturated solution of the stoichiometric mixture in the presence of a high boiling antisolvent, comparatively a very efficient and cheaper method, yielded pure cocrystals. Cocrystals were well characterized by spectroscopic, thermoanalytical tools, X-ray diffraction, and microscopic techniques. A correlation of percentage of cocrystal formation with evaporation rate has been obtained through quantitative analysis using Raman spectrometry. An evaporation rate of <1 mL/min consistently produced pure cocrystal confirmed by Raman and powder X-ray diffraction analysis. Thermokinetic analysis suggests the cocrystal to be more stable than CL-20 with an energy of activation of 65 kcal/mol, higher than CL-20 but inferior to HMX. Significant augmentation in the values of k and A over CL-20 justified a faster decomposition rate. Enhanced insensitivity toward friction and impact forces and higher measured velocity of detonation indicate improved performance on incorporation into high explosive formulations.

Synthesis of 3-azidopiperidine skeleton employing ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether: total synthesis of d-2 receptor agonist (+/-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Lasonkar, Pradeep B.; Gonnade, Rajesh G. (Organic letters, 2018)
The total synthesis of (+/-)-quinagolide, which is a D-2 receptor agonist, was accomplished via a ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether route. Key features of the synthesis include Claisen rearrangement, PPTS (pyridinium p-toluene-sulfonate)-catalyzed one-pot acetal deprotection, followed by a diastereoselective Henry reaction, which enables construction of the required trans ring junction and CAN-mediated regioselective azidoalkoxylation of enol ether. The PPTS-catalyzed intramolecular diastereoselective Henry reaction to fix three contiguous stereocenters on tetrahydronaphthalene and the first-of-its-kind synthesis of the 3-azidopiperidine skeleton, using a CAN -mediated regioselective azidoalkoxylation of enol ether, are important findings of the present work.

Synthesis of quinolinyl based pincer copper (II) complexes: an efficient catalyst system for Kumada coupling of alkyl chlorides and bromides with alkyl Grignard reagents - Pandiri, Hanumanprasad; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2018)
Quinolinamide-based pincer copper(ii) complexes, (N),(N),(N)-{C9H6N-(-N)-C(O)CH2NEt2}CuX [((NNN2Et)-N-Q)CuX (X = Cl, 2; X = Br, 3; X = OAc, 4)], were synthesized by the reaction of ligand ((NNN2Et)-N-Q)-H (1) with CuX2 (X = Cl, Br or OAc) in the presence of Et3N. The reaction of ((NNN2Et)-N-Q)-H with CuX (X = Cl, Br or OAc) also afforded the Cu(ii) complexes 2, 3 and 4, respectively, instead of the expected Cu(i) pincer complexes. The formation of Cu(ii) complexes from Cu(i) precursors most likely occurred via the disproportionation reaction of Cu(i) into Cu(0) and Cu(ii). A cationic complex [((NNN2Et)-N-Q)Cu(CH3CN)]OTf (5) was synthesized by the treatment of neutral complex 2 with AgOTf. On the other hand, the reaction of ((NNN2Et)-N-Q)-H (1) with [Cu(MeCN)(4)]ClO4 produced cationic Cu(i) complex, [((NN)-N-Q(H)N-2(Et))Cu(CH3CN)]ClO4 (6), in good yield. All complexes 2-5 were characterized by elemental analysis and HRMS measurements. Furthermore, the molecular structures of 2, 3 and 4 were elucidated by X-ray crystallography. Complex 4 crystallizes in a dimeric and catemeric pattern. The cationic complex 5 was found to be an efficient catalyst for the Kumada coupling reaction of diverse nonactivated alkyl chlorides and bromides with alkyl magnesium chloride under mild reaction conditions.

Synthetic control on structure/dimensionality and photophysical properties of low dimensional organic lead bromide perovskite - Haris, Muhammed P. U.; Bakthavatsalam, Rangarajan; Shaikh, Samir; Kore, Bhushan P.; Moghe, Dhanashree; Gonnade, Rajesh G.; Sarma, D. D.; Kabra, Dinesh; Kundu, Janardan (Inorganic chemistry, 2018)
Low dimensional lead halide perovskites have attracted huge research interest due to their structural diversity and remarkable photophysical properties. The ability to controllably change dimensionality/structure of perovskites remains highly challenging. Here, we report synthetic control on structure/dimensionality of ethylenediammonium (ED) lead bromide perovskite from a two dimensionally networked (2DN) sheet to a one dimensionally networked (1DN) chain structure. Intercalation of solvent molecules into the perovskite plays a crucial role in directing the final dimensionality/structure. This change in dimensionality reflects strongly in the observed differences in photophysical properties. Upon UV excitation, the 1DN structure emits white light due to easily formed “self-trapped” excitons. 2DN perovskites show band edge blue emission (∼410 nm). Interestingly, Mn2+ incorporated 2DN perovskites show a highly red-shifted Mn2+ emission peak at ∼670 nm. Such a long wavelength Mn2+ emission peak is unprecedented in the perovskite family. This report highlights the synthetic ability to control the dimensionality/structure of perovskite and consequently its photophysical properties.

Stabilization of bis(chlorogermyliumylidene)s within bifunctional PNNP ligand frameworks and their reactivity studies - Sahoo, Padmini; Raut, Ravindra K.; Maurya, Devesh; Kumar, Vikas; Rani, Pooja; Gonnade, Rajesh G.; Majumdar, Moumita (Dalton Transactions, 2019)
The diiminodiphosphine (L-im) and diaminodiphosphines (l-NH and l-NMe) with a bifunctional PNNP ligand framework have been employed to host two [GeCl](+) units leading to the formation of bis(chlorogermyliumylidene) 1-3, respectively. The synthetic route involves a 1:2 stoichiometric reaction between the PNNP ligand and GeCl(2)dioxane and the subsequent addition of two equivalents of chloride abstracting agent. Compound 1 is unstable towards coordinating solvents and Lewis bases, resulting in the displacement of the GeCl unit and the formation of rearranged products 4 and 5. However, the diaminodiphosphine coordinated Ge(ii) bis(monocation)s 2 and 3 proved to be stable and revealed their electrophilic behaviour towards the Lewis bases studied.

Stereoselective construction of deoxy-cruciferane alkaloids by NHC-catalyzed intramolecular annulation of homoenolate with quinazolinone - Ahire, Milind M.; Pol, Mahesh D.; Kavale, Dattatry S; Gonnade, Rajesh G.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2019)
Chiral N-heterocyclic carbene (NHC)-catalyzed intramolecular [3 + 2] annulation of enals with an unactivated imine moiety of quinazolinone via formal homoenolate cycloaddition has been demonstrated. It is an excellent approach for stereoselective syntheses of deoxy-cruciferane alkaloids comprising a biologically important pyrroloindoline scaffold. Notably, this is the first report on the NHC-catalyzed asymmetric intramolecular homoenolate annulation with cyclic N-acyl amidine.

Synthesis and reactivity of a hypersilylsilylene - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Inorganic chemistry, 2019)
Stabilization of an amidinatosilylene with a bulky tris(trimethylsilyl)silyl substituent was realized with the preparation of PhC(NtBu)(2)Si{Si(SiMe3)(3)} (1) from PhC(NtBu)(2)SiHCl2 with K{Si(SiMe3)(3)} in more than 90% yield. The highly deshielded Si-29 NMR resonance (delta = 76.91 ppm) can be attributed to the absence of a pi-donating substituent. The molecular structure of 1 shows a trigonal-planar geometry around the Si-II center with a Si-II-Si-IV bond length of 2.4339(13) angstrom. A series of reactions of 1 with Me3NO, S, Se, and Te were performed. While siloxane derivatives (2 and 3) are obtained from reactions with Me3NO, silachalcogenones (4-6) are formed with other chalcogens. The presence of Si=E (E = S, Se, and Te) bonds in 4-6 have been confirmed by single crystal X-ray studies. Silaoxirane (7) formation was observed when 1 was treated with acetone, demonstrating the importance of the tris(trimethylsilyl)silyl group to kinetically and thermodynamically protect the silaoxirane derivative with less bulky substituents on the C atom.

Self-assembled helical arrays for the stabilization of the triplet state - Nidhankar, Aakash D.; Goudappagouda; Kumari, Divya S. Mohana; Chaubey, Shailendra Kumar; Nayak, Rashmi; Gonnade, Rajesh G.; Kumar, G. V. Pavan; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2020)
Room-temperature phosphorescence of metal and heavy atom-free organic molecules has emerged as an area of great potential in recent years. A rational design played a critical role in controlling the molecular ordering to impart efficient intersystem crossing and stabilize the triplet state to achieve room-temperature ultralong phosphorescence. However, in most cases, the strategies to strengthen phosphorescence efficiency have resulted in a reduced lifetime, and the available nearly degenerate singlet-triplet energy levels impart a natural competition between delayed fluorescence and phosphorescence, with the former one having the advantage. Herein, an organic helical assembly supports the exhibition of an ultralong phosphorescence lifetime. In contrary to other molecules, 3,6-phenylmethanone functionalized 9-hexylcarbazole exhibits a remarkable improvement in phosphorescence lifetime (>4.1 s) and quantum yield (11 %) owing to an efficient molecular packing in the crystal state. A right-handed helical molecular array act as a trap and exhibits triplet exciton migration to support the exceptionally longer phosphorescence lifetime.
Keywords: carbazole; helicity; phenylmethanone; ultralong phosphorescence; waveguiding

Silver-catalyzed cascade cyclization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides: an approach to diverse 3-diarylmethine substituted dihydropyrroles - Shirsath, Sachin R.; Ghotekar, Ganesh S.; Bahadur, Vir; Gonnade, Rajesh G.; Muthukrishnan, M. (Journal of Organic Chemistry, 2020)
A silver-catalyzed cycloisomerization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides to access diverse diarylmethine substituted dihydropyrroles has been disclosed. The reaction pathway involves an intramolecular cascade cyclization of homopropargyl sulfonamides to generate a highly reactive dihydropyrrole intermediate in situ followed by conjugate addition with p-quinone methides. This method provides an efficient and scalable route for the synthesis of 3-diarylmethine substituted dihydropyrroles, in one pot.

Synthesis, crystal structure and Hirshfeld surface analysis of the hydrated form of N’, N-(1,4-phenylenebis(methanylylidene) di(iso-nicotinic hydrazide) - Ingle, Kapil S.; Mohurle, Smital A.; Bairagi, Keshab M.; Shaikh, Tabrez R.; Venugopala, Katharigatta N.; Chandrashekharappa, Sandeep; Gonnade, Rajesh G.; Nayak, Susanta K. (Chemical Data Collections, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The title compound, C<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">20<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">H<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">16<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">N<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">6<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> was synthesized by reflux with isonicotinic hydrazide and terephthaldehyde in ethanol solvent with the acidic condition. The single-crystal X-ray structure determination of the title compound, <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">N, N<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">-(1,4-phenylene bis (methanylylidene) di(iso-nicotinic hydrazide), reveals that the molecule crystallizes in center of symmetry with water molecules (Dihydrated form, C<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">20<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">H<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">16<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">N<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">6<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">.2H<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O) through N-H∙∙∙O and C-H∙∙∙O hydrogen bondings. Further, the crystal structure is stabilized by O-H∙∙∙O and weak C-H∙∙∙N hydrogen bondings with the formation of infinite chain and dimer. Further, surface analysis and fingerprint plot reveal that the significant hydrogen bonding such as H•••O (15.9%) and N•••H (11.4%) interactions play the most crucial role for its molecular packing.

Stabilization of the elusive antimony(I) cation and its coordination complexes with transition metals - Kumar, Vikas; Gonnade, Rajesh G.; Yildiz, Cem B.; Majumdar, Moumita (Angewandte Chemie-International Edition, 2021)
Upon stabilization by 5,6-bis(diisopropylphosphino)acenaphthene to form compound 1, the fugitive antimony (I) cation exhibited nucleophilic behavior towards coinage metals. Compound 1 was strategically synthesized at room temperature from SbCl3, the bis(phosphine), and trimethylsilyl trifluoromethanesulfonate taken in a 1:2:3 ratio, whereby the bis(phosphine) plays the dual role of a reductant and a supporting ligand. The generation of 1 involves two-electron oxidation of the ligand to form a P-P bonded diphosphonium dication. Compound 1 was separated from this dication to give both products in pure form in moderate yields. Despite the overall positive charge, the Sb-I site in 1 was found to bind to metal centers, forming complexes with Au-I, Ag-I and Cu-I. Compound 1 reduced Cu-II to Cu-I and formed a coordination complex with the resulting Cu-I species. The effects of the electron-rich bis(phosphine) and the constrained peri geometry in stabilizing and enhancing the nucleophilicity of 1 have been rationalized through computational studies.
Keywords: antimony(I) cation; coordination modes; nucleophilicity; phosphine ligands; reduction

Synergistic electronic coupling/cross-talk between the isolated metal halide units of zero dimensional heterometallic (Sb, Mn) halide hybrid with enhanced emission - Biswas, Anupam; Bakthavatsalam, Rangarajan; Das, Deep K.; Sam, Jisvin; Mali, Bhupendra P.; Biswas, Chinmoy; Maana, Narugopal; Thomson, Stuart; Raavi, Sai Santosh Kumar; Kurungot, Sreekumar; Gonnade, Rajesh G.; Dutta, Sudipta; et al. (Journal of Materials Chemistry C, 2021)
Heterometallic 0D metal halide hybrids, consisting of more than one kind of metal halide units, are anticipated to manifest synergistic effects on the photo-physical properties of the constituent metal halide units. Such architectures hold great promise for design and development of function-targeted materials. However, heterometallic 0D hybrids, featuring isolated metal halide units, typically do not show any synergistic effects due to large inter-unit spatial separations that inhibit interactions/coupling between the constituent metal halide units. It remains challenging to design synthetic strategies that would support structural modifications to allow synergistic electronic coupling between the metal halide units in heterometallic 0D hybrids. Here, we report synthesis and characterization of heterometallic (Sb, Mn) 0D hybrid, namely Tris SbMnCl, with isolated MnCl5 units, (Sb/Mn)Cl-6 units, dispersed in the organic ligand matrix and layer of dynamic and networked water molecules. Steady state and time resolved emission spectra (TRES) analysis suggests strong synergistic interaction between the isolated metal halide units. Efficient energy transfer from the strongly absorbing Sb centres to emissive Mn centres results in the observed enhanced emission. Proton conductivity measurements together with first-principles calculations suggest the unique role of the networked water molecules in mediating the electronic coupling/energy transfer between the separated metal halide units in Tris SbMnCl hybrid. This report highlights the role of structure/composition of the synthesized heterometallic 0D hybrid in attaining electronic dimensionality higher than 0D through synergistic electronic interaction between the isolated metal halide units.

Synthesis, crystal structure and Hirshfeld surface analysis of a zinc(II) coordination polymer of 5-phenyl-1,3,4-oxadiazole-2-thiolate - Pirimova, Mehribon; Torambetov, Batirbay; Kadirova, Shakhnoza; Ziyaev, Abdukhakim; Gonnade, Rajesh G.; Ashurov, Jamshid (Acta Crystallographica Section E Crystallographic Communications, 2022)
A new zinc coordination polymer with 5-phenyl-1,3,4-oxadiazole-2-thiolate, namely, catena-poly[zinc(II)-bis(μ2-5-phenyl-1,3,4-oxadiazole-2-thiolato)-κ2N3:S;κ2S:N3], [Zn(C8H5N2OS)2]n, was synthesized. The single-crystal X-ray <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/D01712.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">diffraction analysis shows that the polymeric structure crystallizes in the centrosymmetric monoclinic C2/c <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Space_group" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">space group. The ZnII atom is coordinated to two S and two N atoms from four crystallographically independent (L) ligands, forming zigzag chains along the [001] direction. This polymer complex forms an eight-membered [Zn–S–C–N–Zn–S–C–N] chair-like ring with two ZnII atoms and two ligand molecules. On the Hirshfeld surface, the largest contributions come from the short contacts such as <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/V06597.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">van der Waals forces, including H⋯H, C⋯H and S⋯H. Interactions including N⋯H, O⋯H and C⋯C contacts were also observed; however, their contribution to the overall stability of the <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Lattice" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">crystal lattice is minor.
Keywords: 3; 4-oxadiazole-2-thiol; coordination polymer; Hirshfeld surface analysis; crystal structure; zinc complex; 5-phenyl-1

Synthesis of novel rhodamine type anthrone Spiro-lactam (ASL) analogues and evaluation of antiviral activity against dengue and chikungunya viruses - Darole, Ratanamala S.; Bagad, Pooja K.; Gonnade, Rajesh G.; Alagarasu, Kalichamy; Punekar, Madhura; Shukla, Shridhar; Parashar, Deepti; Senthilkumar, Beeran (European Journal of Medicinal Chemistry, 2023)
A series of Rhodamine type Anthrone-Spirolactam (ASL) derivatives Benzylimin-Anthrone-Spirolactam (ASL-1 to ASL-10) and Benzamide-Anthrone-Spirolactam (ASL-11 and ASL-12) were synthesized via a simple condensation reaction between Anthrone Spiro-lactamine (2) and various aromatic aldehyde and acyl chlorides respectively. Since rhodamine-based compounds were reported to have antiviral activity, the ASL derivatives were examined for in vitro antiviral activity against dengue and chikungunya viruses. Among all the analogues, ASL-3, ASL-6, ASL-7, ASL-8, ASL-9 and ASL-10 were the most potent against dengue virus (DENV) and exerted around one log reduction in virus titre under post -treatment conditions. At the same time ASL-3 was effective under cotreatment conditions. Two analogues ASL-6 and ASL-12 exerted anti-chikungunya virus (CHIKV) activity under post -treatment conditions. In silico docking studies revealed that the ASL derivatives interacted with the proteins of DENV and CHIKV. Together, the results suggest the anti-DENV and CHIKV activity of ASL derivatives which may be exploited further for therapeutic purposes.
Keywords: Anthrone Spiro-lactam; Chikungunya virus; dengue virus; Rhodamine

Synthesis of Si(IV)- and Ge(II)-substituted amines, hydrazone, and hydrazine from hypersilyl germylene - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2023)
This study investigates the reactivity of a hypersilyl germylene [PhC-(NtBu)(2)GeSi-(SiMe3)(3)] (1) with various organic compounds including azides, diazoalkanes, 1,2-diphenylhydrazine, and trifluoroacetophenone. The reactivity observed in these reactions is driven by the insertion of the organic fragment between a silicon and germanium bond. This leads to the formation of novel compounds, including an amine featuring three different substituents from three different elements of group 14. When reacting with Me3SiCHN2, we observed the insertion of the diazoalkane fragment in an end-on fashion into the Ge-Si bond. An analogous trend was observed in reactions with 1,2-diphenylhydrazine and trifluoroacetophenone, where the N-N and C-O fragments were inserted into the Ge-Si bond. Multinuclear NMR and single-crystal X-ray diffraction analyses were conducted to characterize the newly synthesized compounds.

Synthesis of imine-phenoxy ligated palladium complexes for norbornene homopolymerization - Birajdar, Rajkumar S.; Gupta, Poonam; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2024)
Metal complexes with tunable ligands play a crucial role in olefin polymerization and impart control over molecular weight, crystallinity, and stereoregularity. We report the single-step synthesis of imine-phenoxy ligands in excellent yields (81-93%). The identity of electronically tuned imine-phenoxy ligands was unambiguously ascertained by using a combination of spectroscopic and analytical methods. These ligands were treated with [Pd(COD)MeCl] in the presence of 2,6-lutidine, resulting in the formation of discrete mononuclear palladium complexes Pd1-Pd4 in excellent yields. 1-2D NMR spectroscopy, mass spectrometry analysis, and single-crystal X-ray diffraction confirmed the identity of the palladium complexes. X-ray analysis revealed a distorted square planar geometry around the palladium center. Proton NMR analysis suggested that the Pd1 catalyst was deshielded, indicating electronically deficient palladium metal compared to the other complexes. Moreover, the Pd1 catalyst showed the highest buried volume percentage (%Vbur = 44.9). When exposed to norbornene, Pd1-Pd4 were found to be active and produced poly(norbornene) (PNB). High-temperature SEC analysis revealed that the electronically deficient and sterically hindered Pd1 catalyst produced the highest molecular weight polymer (PNB 37.4 kDa). Boron and aluminum-based cocatalysts were screened, and MMAO was found to outperform others with high catalytic activity (up to 63.2 x 105 g of PNB (mol Pd)-1 h-1).

Separation of isomers of chiral thiourea derivatives via spontaneous resolution and rationale of molecular recognition - Dwivedi, Astha M.; Gonnade, Rajesh G.; Sahoo, Suban K.; Bedekar, Ashutosh V. (CrystEngComm, 2025)
Enrichment of enantiomers during crystallization of racemic thiourea derivatives was investigated. The spontaneous resolution of a chiral thiourea derivative via preferential crystallization is attributed to thermodynamic stability when molecules of identical chirality bind with each other in the crystal lattice. Single crystal X-ray analysis reveals the interactions responsible for self-recognition of molecules of the same chirality in the unit cell. The tendency of the thiourea derivative to form a conglomerate is supported by IR spectroscopy, thermal analysis and computational studies.

Sila[1]ferrocenophanes with Bulky Substituents - Ajithkumar, V. S.; Bisai, Milan Kumar; Yuvaraj, K.; Gonnade, Rajesh G.; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
In this study, sila[1]ferrocenophanes with sterically bulky groups such as tris(trimethylsilyl) or N-heterocyclic iminato located at the bridging silicon atom are synthesized. The reactions of silicon-bound chloride in Fe(eta 5-C5H4)2SiCl2 (1) with K[Si(SiMe3)3] and silylated N-heterocyclic imine result in sila[1]ferrocenophanes 2 and 3 with bulky silicon- and nitrogen-based substituents at the ansa-bridge via elimination of KCl and Me3SiCl. Subsequently, the reduction of 1 is attempted using 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (popularly known as Mashima reagent), which leads to the elimination of Me3SiCl and generation of 1,4-dihydropyrazine-spanned sila[1]ferrocenophanes (4). All the compounds are structurally characterized.
Keywords: ansa-bridges; ferrocenophanes; hypersilyls; Mashima reagents; N-heterocyclic imines

Studies on the stereoselective synthesis of sacubitril via a chiral amine transfer approach - Sadanande, Megha V.; Thorat, Sagar S.; Sharma, Himanshu; Singh, Geetika; Vanka, Kumar; Gonnade, Rajesh G.; Kontham, Ravindar (Chemistry-An Asian Journal, 2025)
We present a comprehensive account of our efforts directed towards the synthesis of sacubitril, a neprilysin inhibitor used in combination with valsartan and marketed as Entresto (TM). Our initial approach to the formal synthesis of sacubitril employed a chiral pool strategy, utilizing (S)-pyroglutamic acid as a key building block and Cu(I)-mediated Csp2-Csp3 cross-coupling as a key transformation. Further investigations led to the development of chiral amine transfer (CAT) reagents-based stereoselective synthesis. This involved the E-selective construction of gamma-ylidene-butenolide from readily available biphenyl bromide and 4-pentynoic acid, the conversion of this butenolide to its ene-lactam using chiral amine, and substrate-controlled diastereoselective reduction of ene-lactam using Et3SiH or Pd/C, H2 (overall chiral amine transfer) as key transformations. Antipodal lactam intermediates were synthesized using corresponding chiral amines, and the stereochemical outcomes during the ene-lactam reduction with Et3SiH were rationalized by DFT studies.
Keywords: Chiral Amine Transfer (CAT) approach; Chiral pool approach; Sacubitril; stereoselective synthesis

Synthesis and concomitant polymorphs of green fluorescence protein chromophore-anthracene-based fluorescent analogue - Mali, Bhupendra P.; Dabke, Niteen B.; Dash, Soumya R.; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Controlled variations in fluorescence properties hold significant promise for applications in optical sensors, bioimaging, and advanced display devices. However, constructing multicolor fluorescent systems remains a challenge. In this study, we demonstrate the development of multicolor fluorescence by generating polymorphs of a novel green fluorescent protein chromophore analogue, which exhibits distinct photoluminescence emissions in the solid state. The observed emission variations are attributed to differences in molecular conformation due to variations in pi-stacking interactions between the polymorphs. This offers a novel approach to designing materials with tunable fluorescence properties.

Synthesis, crystal structure and Hirshfeld surface analysis of 5-methyl-2-[(1,3-thiazol-2-yl)sulfanyl]-1,3,4-thiadiazole - Kinshakova, Ekaterina; Torambetov, Batirbay; Bharty, Manoj K.; Atashov, Aziz; Rasulov, Abdusamat; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Acta Crystallographica Section E Crystallographic Communications, 2025)
The title compound, C<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">6H<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">5N<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">3S<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">3, consists of two biologically relevant heterocyclic units, suggesting potential biological activity and possible use as a ligand in metal complexation. The compound crystallizes in the monoclinic space group P2<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">1/c and features non-classical intermolecular C—H⋯N hydrogen bonds, along with π–π stacking interactions that contribute to the crystal cohesion. Hirshfeld surface analysis highlights significant intermolecular interactions including, among others, N⋯H/H⋯N, S⋯H/H⋯S, and S⋯C/C⋯S contacts.

Synthesis, crystal structure and Hirshfeld surface analysis of bis[2-amino-5-(ethylsulfanyl)-1,3,4-thiadiazol-3-ium] bis(perchlorato-κO)bis(picolinato-κ2N,O)copper(II) - Khojabaeva, Gulnaz; Torambetov, Batirbay; Gonnade, Rajesh G.; Uzakbergenova, Zamira; Rasulov, Abdusamat; Kadirova, Shakhnoza (Acta Crystallographica Section E, Crystallographic Communications, 2025)

Synthesis, crystal structure, DFT calculation and catalytic activity of a polymer complex of zinc(II) succinate with 2-amino-1,3,4-thiadiazole - Nuralieva, Guzal; Alieva, Mushtariy; Torambetov, Batirbay; Leslee, Denzil Britto Christopher; Senthilkumar, Beeran; Kaur, Simranjeet; Dabke, Niteen B.; Vanka, Kumar; Ashurov, Jamshid; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Journal of Molecular Structure, 2025)
A polymer complex of zinc(II) succinate with a 2-amino-1,3,4-thiadialole ligand, denoted as [Zn2L2(suc)2]n, was synthesized and characterized by NMR, ESI-MS, FTIR, and FT-Raman spectroscopy, TGA, and X-ray crystallography. The polymer complex crystallizes in the orthorhombic noncentrosymmetric Pna21 space group and features a five-coordinate zinc ion in a distorted spherical square pyramidal geometry. The Hirshfeld surface analysis was carried out to evaluate the intermolecular interactions. Additionally, computational studies were also conducted to assess the stability of the Zn polymer complex and analyze the electron density distribution of the HOMO and LUMO. The catalytic activity of our complex was tested, interestingly, that showed good results for Biginelli reactions with distinct substrate scope in good to high yield at mild reaction conditions.
Keywords: DFT; Dihydropyrimidinones; Polymer complex; succinate; Thiadiazole; zinc

Synthesis of diamido N-heterocyclic imines (DAC = NH) via staudinger or reductive N-N bond cleavage approach - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
This report communicates the first examples of N-heterocyclic imines based on electrophilic diamido carbenes (DACs). While 2 is prepared by classical Staudinger synthesis, 4 is obtained via an unusual reductive N-N bond cleavage of an azine by HCl. The exocyclic C=N bond lengths in 2 and 4 are substantially shorter than those based on N-heterocyclic carbenes and cyclic (alkyl)(amino)carbene reflecting the electrophilic character of DACs.

Switchable solid-state emission in GFP chromophore analogue cocrystals via competing AIE and ACQ pathways - Mali, Bhupendra P.; Dabke, Niteen B.; Sharma, Himanshu; Dash, Soumya Ranjan; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2026)
We present a crystal-engineering approach enabling switchable solid-state emission (green -> orange -> quenched) in GFP-chromophore analogue cocrystals. The coformer's electronic and supramolecular effect shifts the photophysical pathway: intramolecular CT in cocrystal-I (green) and cocrystal-III (quenched) and intermolecular CT in cocrystal-II, yielding orange emissions and highlighting cocrystallization's power for tunable luminophores.